Proposal for a uniform nomenclature for defective interfering viruses of vesicular stomatitis virus. - Reichmann, M E (1980)
Defective interfering particles of vesicular stomatitis virus have been named according to their parental derivation and to their genomic length and physical properties. This suggested uniform nomenclature can be adapted for other virus systems.